Circulating endothelial progenitor cells as a marker of left ventricular pump function in ischemic chronic heart failure - A. A. Kremzer (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
The goal of the study was to explore whether the quantity of endothelial progenitor cells (EPCs) associates with ischemic chronic heart failure (CHF) phenotypes.